Stylistic features of simple sentences in Uzbek and English - Rustamov Bobomurod Dilmurodovich (Periodica Journal, 2023)
The style of simple sentences in the Uzbek and English languages has its own characteristics, the communicative-pragmatic aspects of the stylistic means in the Uzbek language are analyzed. As a stylistic phenomenon, it occurs mainly in complex sentences. Antithesis is very common in proverbs and poetry. Stylistics shows how strongly the speaker can express his attitude
Keywords: contrast; Stylistics; proverb